Professor Zdzisław Hellwig 1925 – 2013. Renaissance style giant - Dziechciarz, Józef (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
On 8th November 2013, with great sadness we said goodbye to our dear Master and Teacher, Professor Zdzisław Hellwig. He walked away from us forever. Professor Zdzisław Hellwig (1925 – 2013) was a great man with impressive biography. Primarily professor Zdzisław Hellwig was prominent, widely recognized, eminent scholar of international standing in the field of statistics. His most important works are Elements of probability and mathematical statistics, Linear Regression and its applications in economics and Stochastic approximation. On 8th November 2013, with great sadness we said goodbye to our dear Master and Teacher, Professor Zdzisław Hellwig. He walked away from us forever. Professor Zdzisław Hellwig (1925 – 2013) was a great man with impressive biography. Primarily professor Zdzisław Hellwig was prominent, widely recognized, eminent scholar of international standing in the field of statistics. His most important works are Elements of probability and mathematical statistics, Linear Regression and its applications in economics and Stochastic approximation. His second field of achievements was econometrics. The rich scientific achievements in the field of econometrics of Professor Zdzisław Hellwig cover numerous studies dealing with the theory and application, including modeling of the socio – economic development, economic forecasting, and multidimensional comparative analysis and taxsonometrics. Professor Zdzisław Hellwig has a standing as economist. Professor Zdzisław Hellwig is a precursor of research in the field referred to as sustainable development, and early warning system for the national economy. He is considered pioneer of computer science in Poland. His international activities gave him the global scholar rank. Professor Zdzisław Hellwig was exceptionally gifted teacher and educator with long list of prominent followers. He has notable achievements as an organizer. Achievements of Professor Zdzisław Hellwig were widely acknowledged, both in the home university, countywide and abroad.